Hunt–Vitell’s General Theory of Marketing Ethics Predicts “Attitude-Behaviour” Gap in Pro-environmental Domain - Zaikauskaitė, Laura; Butler, Gemma; Helmi, Nurul F. S.; Robinson, Charlotte L.; Treglown, Luke; Tsivrikos, Dimitrios; Devlin, Joseph T. (Frontiers in Psychology, 2022)
The inconsistency between pro-environmental attitudes and behaviours, known as the “attitude-behaviour” gap, is exceptionally pronounced in scenarios associated with “green” choice. The current literature offers numerous explanations for the reasons behind the “attitude-behaviour” gap, however, the generalisability of these explanations is complex. In addition, the answer to the question of whether the gap occurs between attitudes and intentions, or intentions and behaviours is also unknown. In this study, we propose the moral dimension as a generalisable driver of the “attitude-behaviour” gap and investigate its effectiveness in predicting attitudes, pro-environmental intentions and subsequent behaviours. We do so by using Hunt–Vitell’s moral philosophy-based framework of ethical decision-making, which conceptualises morality as the central decision-making parameter. The results from 557 US MTurk participants revealed that the manipulation of moral dimensions, specifically deontology and teleology, impacted ethical evaluation of presented dilemmas, however, failed to translate into subsequent intentions and behaviours. This finding suggests (i) that the moral dimension has an effect in shaping attitudes toward environmental issues, and (ii) that gap occurs between attitudes and intentions rather than intentions and behaviours. Further investigation of what strengthens and/or overrides the effects of the moral dimension would help understand the reasons why moral attitudes do not always translate into subsequent intentions and behaviours in the pro-environmental domain.